The law and the agitation for state police in Nigeria: Any point of convergence? - Ugochukwu Godspower Ehirim; Ogheneosume Eda; Nwanneka Flora Ehirim; Adeyinka Koiki Owoyele (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: Every major security breach or threat to lives and property in any federating state of Nigeria renews the agitation for the creation of state police in Nigeria. The unitary command of the Nigeria Police Force (NPF) in a constitutional federalism such as Nigeria can at best be an aberration given the expansive unpoliced spaces within the country with their unavoidable security consequences. Purpose/Study Objectives: This paper makes a constructive appraisal of the policing challenges in Nigeria, identifying the centralised command of the NPF as a major obstacle to effective policing in Nigeria. Design/Methodology/Approach: Adopting the doctrinal research methodology, the paper evaluates the current policing structure and its effectiveness. Findings: The paper finds that there is a need to unbundle the NPF, justifying the desirability for the establishment of autonomous state police as an ingredient of true federalism. It recommends the amendment of Sections 214 and 215(4) of the Constitution of the Federal Republic of Nigeria 1999 (CFRN) to align with the provisions of Section 176 of the CFRN and subsisting case-law authorities. Paper Type: Research Article